Kadar BOD dan COD Air Lindi dengan Perlakuan Fitoremidiasi Tanaman Teratai (Nymphaea Sp.) dan Apu-Apu (Pistia stratiotes L.) (Studi Kasus TPA Jetis Purworejo) - Eni Muryani; Ika Wahyuning Widiarti (Jurnal Mineral, Energi dan Lingkungan, 2018)
Phytoremediation is one of alternative methods to remove pollutant in leachate. Leachate from Jetis Landfill was applied in this research. The purposes of the study were to analysis the change of BOD and COD concentration using Nymphaea sp. and Pistia stratiotes L. and to observe plants condition.The research was carried out by laboratory experiment. Tools and materials used in this research were reactors with 50 L capacity, 455 L of leachate, 12 pcs of Nymphaea sp., 120 pcs of Pistia stratiotes L., 12 kg of palm fiber, and 120 kg of gravel. There were 25 reactors consisted of 1 control reactor, 12 reactors with 3 day of resident time (H3) and 12 reactors with 7 days of resident time (H7). Each of reactors is filled with 15-20 L of leachate which consisted of only plant reactors (T or A) and palm fiber, gravel and plant reactors (TIK or AIK).  Each reactor was tested the BOD and COD. Plant conditions were observed daily. Changes of BOD and COD levels for each treatment presented in graphs then analysed descriptively.The results showed that BOD and COD levels of each reactor were lower than control. The difference was relatively small. The AIK-H7 reactor was the most optimum in reducing BOD levels, although the percentage of reduction only 24.11%.  In TIK-H7, the COD level was 576 mg/L, the reduction percentage reached 23,6%. The plant observation, found on the 3rd day of treatment, the leaves of the Nymphaea sp. have begun to decay, while the leaves of the Pistia stratiotes L. have started to dry and turn yellow. On the 7th day the whole plant was died. Phytoremediation with Nymphaea sp. and Pistia stratiotes L. in this research was not maximum to remove BOD and COD in leachate of Jetis Landfill.